Synthesis, in vitro screening and molecular docking of isoquinolinium-5-carbaldoximes as acetylcholinesterase and butyrylcholinesterase reactivators. (1st January 2020) - Malinak, David; Dolezal, Rafael; Hepnarova, Vendula; Hozova, Miroslava; Andrys, Rudolf; Bzonek, Petr; Racakova, Veronika; Korabecny, Jan; Gorecki, Lukas; Mezeiova, Eva; Psotka, Miroslav; Jun, Daniel; et al.
Abstract: The series of symmetrical and unsymmetrical isoquinolinium-5-carbaldoximes was designed and prepared for cholinesterase reactivation purposes. The novel compounds were evaluated for intrinsic acetylcholinesterase (AChE) or butyrylcholinesterase (BChE) inhibition, when the majority of novel compounds resulted with high inhibition of both enzymes and only weak inhibitors were selected for reactivation experiments on human AChE or BChE inhibited by sarin, VX, or paraoxon. The AChE reactivation for all used organophosphates was found negligible if compared to the reactivation ability of obidoxime. Importantly, two compounds were found to reactivate BChE inhibited by sarin or VX better to obidoxime at human attainable concentration. One compound resulted as better reactivator of NEMP (VX surrogate)-inhibited BChE than obidoxime. The in vitro results were further rationalized by molecular docking studies showing future directions on designing potent BChE reactivators. GRAPHICAL ABSTRACT: UF0001